Success Factors for e-learning implementation in Afghan Higher Education institutions - Mahboobi, Sayed Ahmad (Technium Social Sciences Journal, 2021)
There are several factors that need to be considered while planning and designing e-learning programs. This study discusses the success factors that influence e-learning in Afghan higher education Institutions. It is intended to reveal success factors perceived by e-learning dealers and experienced instructors in Afghan Universities. The identified items were ranked by using a convenience sampling survey, gathered data from 72 instructors from several HEIs/Universities in Afghanistan. The results presented five dimensions. These are Awareness (technology pedagogy training, LMS training, Computer skills and competence, and Use and access to MOOCs); Technology (technical support, Access to Internet, and e-learning tools); governance (planning, formal governance structure, collaboration and partnership, and commitment); attitude (control of teaching and content, learning environment, Pedagogy and teaching style, and localization); and e-content development (design and development, and support unit). These factors can contribute to the understanding of e-learning success as a guide, planning tool, and an assessment mode for the efficacy of existing programs.